2015
DOI: 10.1088/0004-637x/814/2/163
|View full text |Cite
|
Sign up to set email alerts
|

IMPLICATIONS FOR THE FORMATION OF BLUE STRAGGLER STARS FROMHSTULTRAVIOLET OBSERVATIONS OF NGC 188

Abstract: We present results of a Hubble Space Telescope far-ultraviolet (FUV) survey searching for white dwarf (WD) companions to blue straggler stars (BSSs) in open cluster NGC 188. The majority of NGC 188 BSSs (15 of 21) are single-lined binaries with properties suggestive of mass-transfer formation via Roche lobe overflow, specifically through an asymptotic giant branch star transferring mass to a main sequence secondary, yielding a BSS binary with a WD companion. In NGC 188, a BSS formed by this mechanism within th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(121 citation statements)
references
References 58 publications
(122 reference statements)
4
116
0
1
Order By: Relevance
“…The data also confirm that the temperature of the hot component is not high enough to be classified as a sub-dwarf, as demonstrated by the slope of the FUV part of the SED. The estimated temperature of the cooler component confirms that it is indeed a BSS, as it is similar to the temperature of other BSSs in NGC188 (Table 1; Gosnell et al 2015) and higher than the turn-off temperature of NGC 188 (∼ 5500 K, based on the turn-off color). The opti-cal region of the SED is fitted well by the combined flux from the two components.…”
Section: Uvit Datasupporting
confidence: 79%
See 3 more Smart Citations
“…The data also confirm that the temperature of the hot component is not high enough to be classified as a sub-dwarf, as demonstrated by the slope of the FUV part of the SED. The estimated temperature of the cooler component confirms that it is indeed a BSS, as it is similar to the temperature of other BSSs in NGC188 (Table 1; Gosnell et al 2015) and higher than the turn-off temperature of NGC 188 (∼ 5500 K, based on the turn-off color). The opti-cal region of the SED is fitted well by the combined flux from the two components.…”
Section: Uvit Datasupporting
confidence: 79%
“…The hot star is about 3 times more luminous than hot B sub-dwarfs (T ef f > 27000 K L ∼ 10 L ) and blue horizontal branch stars (L ∼ 10 L ) (Heber 2016). Also, the FUV luminosity is found to be much higher than those of the BSS+WD of similar temperature (e.g., WOCS-4540, WOCS-5379) as estimated by Gosnell et al (2015). These two observations suggest that the hot component cannot be a WD or a sub-dwarf, therefore we speculate that it is a post-AGB star or a post-HB star (depending on the initial mass of the star).…”
Section: Uvit Datamentioning
confidence: 55%
See 2 more Smart Citations
“…Nine of our FUV selected BSs are optically bright, the remaining FUV bright BS is optically faint and located in the MS turn-off region. Its FUV excess might be explained with a WD companion which contributes flux to the FUV (see Gosnell et al 2015, who found BS-WD binaries in the old open cluster NGC 188)…”
Section: Blue Stragglersmentioning
confidence: 99%